Implications of Climate Change Driven Flooding in the McCaslin Brook Watershed - Pollari, Tim; Lamb, Matt; Lee, Danielle; Powell, Holly (My University, 2011)
Locate parcels affected by flooding due to changes in precipitation in the McCaslin Brook Watershed in Oconto County, WI. A series of precipitation scenarios based on climate models are evaluated to assess local climate impact. Maps and charts are generated to guide in infrastructure development.
Includes Figures, Tables, Maps, Appendices and Bibliography.
Keywords: Climate Change; Climate Models; McCaslin Brook Watershed; Flooding